2013
DOI: 10.1016/j.ijmm.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clinical Campylobacter jejuni isolates with special emphasis on lipooligosaccharide locus class, putative virulence factors and host response

Abstract: Recent studies have indicated a role of the lipooligosaccharide (LOS) of Campylobacter jejuni in the severe neurological Guillain Barré syndrome, as well as in development of more severe symptoms of acute enteritis. We evaluated the role of the LOS locus class in C. jejuni infection among 163 enteritis patients. The prevalence of LOS locus classes differed according to the origin of the isolates. Furthermore, LOS locus classes A and B were significantly associated with susceptibility or resistance to ciproflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
5
22
1
Order By: Relevance
“…The LOS locus class C was the most common in both sources followed by the classes E and H, which is in line with the results from other studies on human isolates [5, 8, 15]. By a combined analysis of LOS locus classes and the Sma I restriction patterns, we sought to identify potential differences in transmission of isolates with different LOS locus classes between the Swedish chickens and humans as well as from unknown sources.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The LOS locus class C was the most common in both sources followed by the classes E and H, which is in line with the results from other studies on human isolates [5, 8, 15]. By a combined analysis of LOS locus classes and the Sma I restriction patterns, we sought to identify potential differences in transmission of isolates with different LOS locus classes between the Swedish chickens and humans as well as from unknown sources.…”
Section: Discussionsupporting
confidence: 77%
“…In this material however, the prevalence of fucP was only slightly higher than 50 % among the human and chicken isolates. In our previous studies we found this particular gene to be present in 49 % of isolates from enteritis patients and in 23 % of isolates from bacteremia patients in Finland [2, 8]. Together these results suggest that L-fucose utilization by fucP hardly is a prerequisite for colonization of chickens or for causing infections in humans.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Although C. jejuni has a limited ability to metabolize sugars, the organism possesses a large number of enzymes involved in the biosynthesis of carbohydrates which are then incorporated into its peptidoglycan (PG), lipooligosaccharides (LOS), capsular polysaccharides (CPS) and both N-and O-linked glycoproteins. Recent studies have indicated a role of the lipooligosaccharide (LOS) of C. jejuni in virulence, particularly the severe neurological Guillain Barré syndrome (Ellström et al, 2013;Pike et al, 2013). LOS and CPS are also involved in the interaction between Campylobacter and the human innate and acquired immune system.…”
Section: Epidemic Strainmentioning
confidence: 99%